An introduction to nonlinear finite element analysis - Reddy, J. N. (Junuthula Narasimha), 1945- (Oxford University Press, 2004)
Reddy presents the theory and computer implementation of the finite element method as applied to nonlinear problems of heat transfer and similar field problems, fluid mechanics (flows of incompressible fluids), and solid mechanics (elasticity, beams and plates).